Physicochemical Characterization and Water Quality Feasibility across Three Source Water Types in the Ciputat Area, South Tangerang - Vetty Megantari; Nurul Amilia; Nita Rosita; Wahyu Permata; Fitriah Hatiningsih (Journal of Biotropical Research and Nature Technology, 2026)
This study aims to characterize the physicochemical quality and assess the water quality feasibility across three source Water Source Type used in parallel within the Ciputat area, South Tangerang, namely tap water from public facilities and residential areas (Type I, n = 4), tap water from university buildings at Universitas Islam Negeri Syarif Hidayatullah Jakarta (Type II, n = 8), and drinking water from refill stations (Type III, n = 8), evaluated against the Ministry of Health Regulation (Permenkes) No. 2 of 2023. In situ parameters included pH, temperature, dissolved oxygen (DO), turbidity, total dissolved solids (TDS), and salinity. Laboratory analyses encompassed iron (Fe) and manganese (Mn) determination via atomic absorption spectrophotometry (AAS) across all three Water Source Types, as well as ammonia (N-NH3) and phosphate (P-PO4) analysis using UV-Vis spectrophotometry specifically for Water Source Types II and III. The results indicated that the turbidity of all samples (3.70–23.81 NTU) exceeded the maximum permissible limit of less than 3 NTU across all three water sources. Whereas, based on the WHO guideline, drinking water turbidity should not exceed 5 NTU [1]. The campus tap water was dominated by acidic pH levels (5.40–7.50), with six out of eight buildings falling below the minimum threshold of 6.5. Iron levels in all samples were below the method detection limit, whereas manganese levels exceeded the quality standard of 0.1 mg/L exclusively in Water Source Type I (0.336–0.853 mg/L), which is consistent with geogenic sources in shallow groundwater. The N-NH3 and P-PO4 concentrations in all samples complied with the specific parameter standards of Permenkes No. 2 of 2023. In conclusion, no matrix satisfied all parameters simultaneously. Hence, corrective interventions must be tailored to the dominant characteristics of each respective water source.